Christel Lane: The Cultivation of Taste. Chefs and the Organization of Fine Dining - Jaine, Tom (Petits Propos Culinaires, 2015)
Christel Lane: The Cultivation of Taste. Chefs and the Organization of Fine Dining: Oxford University Press, 2014: 368 pp., hardback.